Through the huge, brown eyes a Filipina's look at female gender roles in Kaichou wa Maid-Sama! and Toradora! - Aldana, Claudine Lesbañes 1993-; Vinculado, Jane O.; University of the Philippines. College of Mass Communication (2013)
"This study aims to find out how female tsundere Japanese anime characters are perceived in the context of the Philippines. The female pretogonists were analyzed to see if their roles promote gender stereotypes or liberate characters. All the episodes from two anime series were selected for the study. Kaichou wa Maid-sama! and Toradora! Using textual analysis as the methodology for this research, each episode was analyzed according to three themes: (1) their roles at home, in school and at work, (2) their traits, whether masculine or feminine, and (3) their relations to the other characters in the series. Armed with socialist feminism and knowledge of Philippine gender roles, these themes were scrutinized closely to see of the female protagonists in the series were used to question the stereotypes of women, or to uphold gender roles apparent in the Philippines. Fromt his, the researcher has found out that women in these series possess masculine traits that deviate from the cultural norms in the Philippines. They are independent and capable of fighting for what they want. However, the females are still subservient when it comes to their father and lover, seeking approval and support from them because of their relationship with them."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Women on television; Animated television programs; Sex roles on television; Stereotypes(Social psychology).; Social norms -- Philippines